Comparison of the quality of life of elderly people practicing physical activities and competitive sports games. - Júnior, Valter Mariano dos Santos; Stocco, Marieli Ramos; Lourenço, Márcia Regina Aversani; Casonatto, Juliano; Teixeira, Denilson de Castro (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Background: With increasing life expectancy and decreasing fertility rate the aging population is growing significantly, requiring actions that enable melhoraras health and quality of life of older people. Objective: This study aimed compare the perception of quality of life among elderly participants of a traditional exercise program performed in a Basic Health Units (EF-BHU) with practitioners of competitive sports that participate in the Senior Regional Games (JORI). Methods: The study involved 98 subjects of both sexes, aged over 60 years living in Votuporanga, SP, Brazil. Information have been raised as to the sociodemographic profile, health status, gender, age and quality of life through the WHOQOL-BREF questionnaire and WHOQOL-OLD. The numerical variables (age and education) were compared (inter-group) using the test Mann-Whitney. The chi-square test was used to analyze the associations in categorical variables. The “scores” of quality of life questionnaire (numerical) were classified, so that those subjects with levels located at quartile 4 (Q4) were designated “high” and peers located in other quartiles (Q1, Q2 and Q3) designated “low”. For associations “2x2” (physical activity practiced x quality of life) was employed again the chi-square test. Variables with P<0.2 were subjected to the logistic regression model (Univariate) Poisson with robust adjustment of variance. Then, those variables that were statistically significant (P<0.05) in the univariate model, were subjected to the adjusted model. Results: The results indicate that the elderly have JORI median age less than EF-UBS elderly (64 versus 67 years, p <0.01) higher education (10 versus 02 years, p <0.01) and have more positive perceptions related to their housing, income and health. Regarding the quality of life of the JORI elderly have more positive perceptions in various dimensions in relation to EF-UBS elderly). Conclusion: We can conclude that elderly JORI, in general, have more positive perceptions of quality of life in relation to the EF-UBS elderly.